1993
DOI: 10.1111/j.1559-1816.1993.tb01064.x
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of Trait Attributions Associated with Eyeglasses, Men's Facial Hair, and Women's Hair Length1

Abstract: This research investigated the effects of men's eyeglasses and facial hair and women's eyeglasses and hair length on the traits associated with facial schemata. One hundred and thirty‐five introductory psychology students rated Photo‐IdentTM composites of stimulus persons on 20 adjectival continua. A factor analysis of the scores extracted three factors: Social Value, Social Forcefulness, and Mental Competence. Eyeglasses on both the men and women were associated with attributions of diminished forcefulness an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
2
3

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 29 publications
2
39
2
3
Order By: Relevance
“…Thus, growing a beard will probably change a person's appearance more than shaving one off will. Although, as with the eyeglasses, determining precise effects from these data is difficult, the results are consistent with the social judgments about beards that were obtained in Experiment 2 and with the results of previous studies (e.g., Terry & Krantz, 1993).…”
Section: Discussionsupporting
confidence: 88%
“…Thus, growing a beard will probably change a person's appearance more than shaving one off will. Although, as with the eyeglasses, determining precise effects from these data is difficult, the results are consistent with the social judgments about beards that were obtained in Experiment 2 and with the results of previous studies (e.g., Terry & Krantz, 1993).…”
Section: Discussionsupporting
confidence: 88%
“…Results obtained when this metaphor is applied in Western cultures indicate that men and women with gray or thinning hair are deemed less attractive; that long hair and facial hair on men represents nonconformity, creativity and sexuality, and that specific hair colors communicate particular social meanings, such as femininity or elitism (Butler et al, 1998;Cash, 1990;Clayson and Maughan, 1986;Cooper, 1971;Franzoi et al, 1990;Larsen and White, 1974;Lawson, 1971;McCracken, 1995;Terry and Krantz, 1993) (see Table 1). Although not so stated in the social psychology literature, these meanings appear rooted in both culture and biological phenomena -for example, in Western cultures gray hair is associated with aging, and ultimately death.…”
Section: Social Psychological Metaphors For Hairmentioning
confidence: 92%
“…Broyde, 1991;Butler et al, 1998;Cash, 1990;Clayson and Maughan, 1986;Cooper, 1971;Franzoi et al, 1990;Larsen and White, 1974;Lawson, 1971;Terry and Krantz, 1993;Zipkin, 1999).…”
Section: Product Category/consumption Areamentioning
confidence: 99%
“…Just as in the examples above, other studies on stereotyping and facial appearance have shown that judgments made by subjects are highly consensual (Berry & Zebrowitz, 1988;Browillow & Zebrowitz;Goldstein, Chance, & Gilbert, 1984; Kahlick, Zebrowitz, Langlois, & Johnson, 1988;Perrett & Yoshikawa, 1994;Shoemaker, South, & Lowe, 1973;Terry & Davis, 1976;Terry & Krantz, 1993;Zebrowitz, Voinescu, & Collins, 1996;Zebrowitz & McDonald, 1991). Subjects make these judgments in.…”
mentioning
confidence: 99%
“…It may be that an individual's behavior, in this regard, is reinforced by the fact that many times he or she is correct and this reinforces the practice o f physiognomy. Terry and Krantz (1993) empirically evaluated the salient features involved in physiognomy by varying different features o f the face. They specifically examined the effects o f eyeglasses, men's facial hair, and women's hair length on the traits attributed to facial appearance.…”
mentioning
confidence: 99%